2013
DOI: 10.1038/ncomms2935
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer assembly of vertically conducting graphene devices

Abstract: Graphene has various potential applications owing to its unique electronic, optical, mechanical and chemical properties, which are primarily based on its two-dimensional nature. Graphene-based vertical devices can extend the investigations and potential applications range to three dimensions, while interfacial properties are crucial for the function and performance of such graphene vertical devices. Here we report a general method to construct graphene vertical devices with controllable functions via choosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 28 publications
5
98
1
Order By: Relevance
“…While this MR remained quite low compared to expectations and previous reports, interestingly, the authors provided data for a set of about 10 samples, which confirmed this trend. In 2013, a study by Meng et al and Cheng et al, detailed in two papers [21,22], presented the data for Co/graphene/Co vertical structures with a similar conclusion: MTJs based on monolayer CVD graphene showed an MR of 0.7%, whilst those based on bilayer graphene showed an MR of up to 1%. After 2014, these different works were further developed in follow-up papers, where the graphene layer is still transferred by wet chemistry, but with slight changes to the device structure in order to extract complementary information [23,32,41].…”
Section: Working With Exfoliated and Transferred Graphenementioning
confidence: 84%
See 1 more Smart Citation
“…While this MR remained quite low compared to expectations and previous reports, interestingly, the authors provided data for a set of about 10 samples, which confirmed this trend. In 2013, a study by Meng et al and Cheng et al, detailed in two papers [21,22], presented the data for Co/graphene/Co vertical structures with a similar conclusion: MTJs based on monolayer CVD graphene showed an MR of 0.7%, whilst those based on bilayer graphene showed an MR of up to 1%. After 2014, these different works were further developed in follow-up papers, where the graphene layer is still transferred by wet chemistry, but with slight changes to the device structure in order to extract complementary information [23,32,41].…”
Section: Working With Exfoliated and Transferred Graphenementioning
confidence: 84%
“…Another striking issue concerned the out-of-plane electrical conduction in devices encompassing only a graphene layer between the two ferromagnetic electrodes, with still no experimental consensus yet on the role of the graphene spacer. Some of the earlier mentioned studies reported on graphene acting mainly as a metallic spacer [20,21,24,32,39], whilst other studies reported on it acting as a tunnel barrier [14,24,28]. One study [25] even reported that its role varied with temperature.…”
Section: Spin Filtering At the Fm/graphene Interfacementioning
confidence: 99%
“…Recently, graphene has been explored as a barrier for spin transport, where TMR and spin filtering effects have been observed [9][10][11][12][13][14][15][16][17][18][19], including the bias dependence of the TMR [20]. However, the absence of a bandgap in semi-metallic and low resistive graphene has led to an increasing demand for an insulating 2D crystal [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…www.mdpi.com/journal/applsci of the exterior surface as the basis for assembly [15,16]. Through added layers deposited onto the HNTs, the pattern of released substances can be further controlled, enabling delayed or inhibited release [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Through added layers deposited onto the HNTs, the pattern of released substances can be further controlled, enabling delayed or inhibited release [13][14][15][16]. For coating of the HNT surface, a layering method is commonly used to achieve the desired coatings onto the exterior surface, using the inherent charge differential between the layers of the nanotubes as the basis for these coatings [16,17].…”
Section: Introductionmentioning
confidence: 99%